Watermark Detection in Impulsive Noise Environment Based on the Compressive Sensing Reconstruction - B. Lutovac; M. Dakovic; S. Stankovic; I. Orovic (Radioengineering, 2017)
The watermark detection procedure for images corrupted by impulsive noise is proposed. The procedure is based on the compressive sensing (CS) method for the reconstruction of corrupted pixels. It is shown that the proposed procedure can extract watermark with a moderate impulsive noise level. It is well known that most of the images are approximately sparse in the 2D DCT domain. Moreover, we can force sparsity in the watermarking procedure and obtain almost strictly sparse image as a desirable input to the CS based reconstruction algorithms. Compared to the state-of-the-art methods for impulse noise removal, the proposed solution provides much better performance in watermark extraction.